2017
DOI: 10.1097/ede.0000000000000614
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Exposure to PM2.5 and Mortality Among Older Adults in the Southeastern US

Abstract: Background Little is known about what factors modify the effect of long-term exposure to PM2.5 on mortality, in part because in most previous studies certain groups such as rural residents and individuals with lower socioeconomic status (SES) are under-represented. Methods We studied 13.1 million Medicare beneficiaries (age ≥65) residing in seven southeastern US states during 2000–2013 with 95 million person-years of follow-up. We predicted annual average of PM2.5 in each zip code tabulation area (ZCTA) usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
98
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(109 citation statements)
references
References 37 publications
8
98
1
2
Order By: Relevance
“…By comparison, we found a hazard ratio of 1.021 (1.019, 1.022) using Cox proportional hazard model adjusting for the same set of covariates. 17 We further found that an increase in the percentage of truncation from 1% to 5% resulted in a decrease in the effect estimate for PM 2.5 (eFigure 9; http://links.lww.com/EDE/B260). …”
Section: Resultsmentioning
confidence: 62%
See 3 more Smart Citations
“…By comparison, we found a hazard ratio of 1.021 (1.019, 1.022) using Cox proportional hazard model adjusting for the same set of covariates. 17 We further found that an increase in the percentage of truncation from 1% to 5% resulted in a decrease in the effect estimate for PM 2.5 (eFigure 9; http://links.lww.com/EDE/B260). …”
Section: Resultsmentioning
confidence: 62%
“…By comparison, some effect modification using hazard difference (e.g., hospital admissions, dual eligibility) showed the same direction as hazard ratios, whereas some (e.g., age) does not. 17 In addition, we found that black people with dual eligibility had a hazard difference of 1.60 × 10 −3 (1.21, 1.99) × 10 −3 . Black people age 75–84 years old had a hazard difference of 2.28 × 10 −3 (1.80, 2.75) × 10 −3 , suggesting an increase in susceptibility among these populations.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…4,[7][8][9] Studies with large cohorts have investigated the relationship between long-term exposures to PM 2.5 and ozone and mortality 4,[9][10][11][12][13] ; others have estimated the health effects of fine particles at low concentrations (e.g., below 12 μg per cubic meter for PM 2.5 ). [14][15][16][17][18] However, most of these studies have included populations whose socioeconomic status is higher than the national average and who reside in well-monitored urban areas. Consequently, these studies provide limited information on the health effects of long-term exposure to low levels of air pollution in smaller cities and rural areas or among minorities or persons with low socioeconomic status.…”
mentioning
confidence: 99%